Economic cost analysis of door‐to‐door community‐based distribution of HIV self‐test kits in Malawi, Zambia and Zimbabwe. (25th March 2019) - Mangenah, Collin; Mwenge, Lawrence; Sande, Linda; Ahmed, Nurilign; d'Elbée, Marc; Chiwawa, Progress; Chigwenah, Tariro; Kanema, Sarah; Mutseta, Miriam N; Nalubamba, Mutinta; Chilongosi, Richard; Indravudh, Pitchaya; et al.
Abstract: Introduction: HIV self‐testing (HIVST) is recommended by the World Health Organization in addition to other testing modalities to increase uptake of HIV testing, particularly among harder‐to‐reach populations. This study provides the first empirical evidence of the costs of door‐to‐door community‐based HIVST distribution in Malawi, Zambia and Zimbabwe. Methods: HIVST kits were distributed door‐to‐door in 71 sites across Malawi, Zambia and Zimbabwe from June 2016 to May 2017. Programme expenditures, supplemented by on‐site observation and monitoring and evaluation data were used to estimate total economic and unit costs of HIVST distribution, by input and site. Inputs were categorized into start‐up, capital and recurrent costs. Sensitivity and scenario analyses were performed to assess the impact of key parameters on unit costs. Results: In total, 152, 671, 103, 589 and 93, 459 HIVST kits were distributed in Malawi, Zambia and Zimbabwe over 12, 11 and 10 months respectively. Across these countries, 43% to 51% of HIVST kits were distributed to men. The average cost per HIVST kit distributed was US$8.15, US$16.42 and US$13.84 in Malawi, Zambia and Zimbabwe, respectively, with pronounced intersite variation within countries driven largely by site‐level fixed costs. Site‐level recurrent costs were 70% to 92% of full costs and 20% to 62% higher than routine HIV testing services (HTS) costs. Personnel costs contributed from 26% to 52% of total costs across countries reflecting differences in remuneration approaches and country GDP. Conclusions: These early door‐to‐door community HIVST distribution programmes show large potential, both for reaching untested populations and for substantial economies of scale as HIVST programmes scale‐up and mature. From a societal perspective, the costs of HIVST appear similar to conventional HTS, with the higher providers' costs substantially offsetting user costs. Future approaches to minimizing cost and/or maximize testing coverage could include unpaid door‐to‐door community‐led distribution to reach end‐users and integrating HIVST into routine clinical services via direct or secondary distribution strategies with lower fixed costs.